Permanent Grant of Land Certificate for Adat People, is it Possible? - Zamil, Yusuf Saepul; Sekarwati, Supraba; Pujiwati, Yani; Nurlinda, Ida (International Journal of Criminology and Sociology, 2021)
Adat peoples mean the original inhabitants or the first inhabitants of a country or the earliest population’s descendants lived in the area. All this time, adat people in Indonesia have always been marginalized and banished from their homeland. Companies that acquired investment permits from the government often dismiss the adat peoples for their interests. This dismissal occurs due to the absence of proof for the collective land ownership (ulayat land), which is used and utilized collectively and communally. This article discusses the possibility of permanently grant the land certificates to provide legal protection for the adat peoples. Granting a certificate of land rights is possible if the government changes the land registration system from the negative to the positive system (torrens system). Adat peoples may acquire land certificates if they are considered as a legal entity. According to Indonesian law, only individuals or legal entities can register ownership of land. To make adat people a legal entity is by making regulations by the Minister of Agrarian and Spatial Planning which states that adat people in certain areas who have met the requirements are declared as legal entities.